Green classroom vs. classroom – Influence of teaching approaches, learning settings, and state emotions on environmental values of primary school children. Issue 2 (3rd April 2019) - Glaab, Sabine; Heyne, Thomas
ABSTRACT: We evaluated environmental values of primary school children during a one-day program at a wildlife park and compared the outcomes concerning two different forms of instruction (teacher-centered, student-centered) as well as two different surroundings of learning settings (wildlife park, school) while observing state emotions. A total of 441 primary school children (average age 8.87 ± 0.56 years) learned about the importance of preserving the habitat of the European wildcat. A questionnaire based on an established model was administered. Students' preservation values changed significantly at the wildlife park as well as at school with no significant differences between forms of instruction and state emotions overall.